Comparison of clinicopathologic characteristics and survival outcomes between invasive IPMN and invasive MCN: A population-based analysis - Yang, Zhen; Shi, Guangjun (Frontiers in Oncology, 2022)
Abstract Background: Intraductal papillary mucinous neoplasm (IPMN) and mucinous cystic neoplasm (MCN) are two main histological subtypes of pancreatic cystic neoplasms with rapid increasing incidence recently. The natural histories, treatment patterns and survival outcomes of invasive IPMN and invasive MCN have not been well explored. Methods: Patients with a diagnosis of invasive IPMN and invasive MCN in the SEER database from 2000 through 2018 were retrospectively identified. Multivariable Cox regression analysis was conducted to determine independent risk factors associated with overall survival (OS). Subgroup analyses of survival outcomes for invasive IPMN and invasive MCN were conducted. The OS for invasive IPMN was compared between patients who underwent surgery alone and those who received surgery plus chemotherapy by propensity score matching (PSM). Results: A total of 2505 patients were included, of whom 2300 were diagnosed with invasive IPMN, and 205 were diagnosed with invasive MCN. Half of invasive IPMN (48.4%) and three-quarters of invasive MCN (76.1%) patients were female. Of all patients, both the overall survival (OS) and cancer-specific survival (CSS) were significantly better in the invasive MCN cohort compared to the invasive IPMN cohort. In subgroup analyses, while invasive MCN experienced better OS compared to invasive IPMN in the subgroups of patients with local-regional disease, the survival advantages disappeared in patients at distant stage. In addition, surgery plus chemotherapy in invasive IPMN patients was associated with significantly better survival compared to surgery alone after PSM. Conclusion: We examined the demographic and clinical characteristics between invasive IPMN and invasive MCN patients using large population-based analysis. Although the OS is significantly better for invasive MCN versus invasive IPMN, the difference disappeared in patients with distant disease. A combination of surgery and chemotherapy in selected invasive IPMN patients could confer survival benefits compared to surgery alone.